Growing community, food sovereignty, and health - Sara Shostak; Anna Kehoe; Jolie Black; Rachel Bindman (Journal of Agriculture, Food Systems, and Community Development)
Produce prescription programs are an emerging strategy for making diet and nutrition central to efforts to improve population health. Although they have multiple potential implications for local food systems, assessments of produce prescription programs too rarely consider the perspectives of food producers. This paper reports on a mixed-methods case study of VegRx, a farm-based produce prescription program in Waltham, Massachusetts. Drawing on interviews with both farmers and clinicians, we first explore how produce prescription programs can be aligned with the missions of community farms, including increasing access to healthy, locally grown food, building relationships with and among underserved community members, and advancing food sovereignty. Based on quantitative data from pre- and post-program surveys, we then assess the outcomes of VegRx for program participants; these include significant improvements in their access to healthy and desired foods, vegetable and fruit consumption, and both physical and mental health. We conclude with recommendations for a broader understanding—and assessment—of produce prescription programs, to take into account not only their important capacity to improve diet and nutrition, but also to bring together local farms, health-care providers, and communities in support of food sovereignty and population health.